New insight into the taxonomy of Cephaloziellaceae (Marchantiophyta): the family of the smallest higher plants on Earth - Bakalin, Vadim A.; Maltseva, Yulia D.; Klimova, Ksenia G.; Nguyen, Van Sinh; Choi, Seung Se; Troitsky, Aleksey V. (Frontiers in Plant Science, 2024)
An analysis of the phylogeny of Cephaloziellaceae was carried out based on trees constructed for previously and newly obtained sequences of five genes: nuclear ITS1–2 and chloroplast trnL–F, trnG, rbcL, and psbA. Phylogenetic trees inferred from different genes are congruent for the main details; however, the position of several taxa is variable. As a result, a new phylogenetic system of the family was proposed. The narrow genus concept seems to be more appropriate for the family. Cephaloziella spinicaulis is segregated into the new genus Douiniella, the generic status for Prionolobus and Metacephalozia is confirmed, and the dubious generic status of Kymatocalyx is substantiated. The generic independence of Cylindrocolea from Cephaloziella s. str. is confirmed. The small amount of data hinders the description of two more genera from Cephaloziella s.l.